2004
DOI: 10.1167/iovs.03-1343
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Inhibits Transepithelial Chloride Secretion across Bovine Ciliary Body/Epithelium

Abstract: The results suggest that cAMP plays a crucial role in modulating Cl(-) secretion across the ciliary epithelium. The effect is possibly mediated, at least in part, by the regulation of the permeability of gap junctions between pigmented and nonpigmented ciliary epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…Moreover, gap junctions inhibitors disrupts electrical communications between smooth muscle cells 25) and thus this fact could be blocking the RCs, as observed in other study. 8,14,23) Although heptanol is relatively reliable in blocking gap junctions in a selective mode, 16,17,26,27) 31,32) bovine oocytes, 33) ciliary body 34) and human HeLa cells, 35) heptanol has been either shown 30,32) or assumed 33,34) to act as specific gap junction blocker over a range of concentration (Յ10 mmol/l), substantially larger than those used in our study (0.5 mmol/l). Taken together, the results obtained in this study suggest that heptanol, acting via gap junctions, inhibits the RCs and reveal an important participation of these junctions on oscillations.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, gap junctions inhibitors disrupts electrical communications between smooth muscle cells 25) and thus this fact could be blocking the RCs, as observed in other study. 8,14,23) Although heptanol is relatively reliable in blocking gap junctions in a selective mode, 16,17,26,27) 31,32) bovine oocytes, 33) ciliary body 34) and human HeLa cells, 35) heptanol has been either shown 30,32) or assumed 33,34) to act as specific gap junction blocker over a range of concentration (Յ10 mmol/l), substantially larger than those used in our study (0.5 mmol/l). Taken together, the results obtained in this study suggest that heptanol, acting via gap junctions, inhibits the RCs and reveal an important participation of these junctions on oscillations.…”
Section: Discussioncontrasting
confidence: 52%
“…Cl -secretion from NPE cells is mediated by Cl -channels, whose activity is controlled by intracellular cyclic adenosine monophosphate (cAMP), which is increased by P2Y 6 receptor activation (51,52). It has been reported that cAMP causes both an increase (52-54) and decrease of Cl -secretion (55)(56)(57). One explanation for these controversial reports might be related to TGFβ-mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Because P2Y 6 receptor activation causes TGFβ production (59, 60), UDP may suppress Cl -secretion by producing both TGFβ and cAMP. Another possible candidate is the gap junction because it mediates intercellular connections between PE and NPE cells, which is essential for transepithelial Cl -transport (56,61). Elevation of cAMP caused intercellular uncoupling between PE and NPE cells (56 ]i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent detailed characterization of its effects on vascular smooth muscle cells (Matchkov et al, 2004), it was shown that heptanol, over the range of concentrations used in our study (0.5-2.0 mM), potently increased the input resistance of the cells and desynchronized their [Ca 2+ ]i oscillations, indicating that it powerfully uncoupled the cells. Indeed, in several recent studies carried out on a range of cell / tissue preparations, including mouse heart (Knapp et al, 2005), rabbit heart (Przyklenk et al, 2005), bovine oocytes (Atef et al, 2005), ciliary body (Do et al, 2004), and human HeLa cells (Bader and Weingart, 2004), heptanol has been either shown (Knapp et al, 2005;Atef et al, 2005) or assumed (Do et al, 2004;Bader and Weingart, 2004) to act as a specific gap junction blocker over a range of concentrations (≤ 10 mM), substantially larger than those used in our study (≤ 2 mM). In our own studies on mammalian vas deferens, the concentrations of heptanol employed to study the effects of uncoupling have not been found to affect resting potential (guinea-pig vas deferens: Manchanda and Venkateswarlu, 1997; rat vas deferens: Palani and Manchanda, unpublished observations), indicating a lack of effect on membrane ion channels.…”
Section: Role Of Cell-to-cell Coupling In Na-induced Contractionmentioning
confidence: 66%